An automated verification workflow for planned lighting setups using BIM. - Walch, Andreas; Krösl, Katharina; Luksch, Christian; Pichler, David; Pipp, Thomas; Schwärzler, Michael (My University, 2018)
The use of Building Information Modeling (BIM) methods is becoming more and more established in the planning stage, during the construction, and for the management of buildings. Tailored BIM software packages allow to handle a vast amount of relevant aspects, but have so far not been covering specialized tasks like the evaluation of light distributions in and around a 3D model of a building. To overcome this limitation, we demonstrate the use of the open-source IFC format for preparing and exchanging BIM data to be used in our interactive light simulation system. By exploiting the availability of 3D data and semantic descriptions, it is possible to automatically place measurement surfaces in the 3D scene, and evaluate the suitability and sustainability of a planned lighting design according to given constraints and industry norms. Interactive visualizations for fast analysis of the simulation results, created using state-of-the-art web technologies, are seamlessly integrated in the 3D work environment, helping the lighting designer to quickly improve the initial lighting solution with a few clicks.
Keywords: Building Information Modeling; Gebäudeplanung; Lichtverteilung; 3D-Modell